America's state quarters : the definitive guidebook to collecting state quarters - Ganz, David L.; Ganz, David L. (New York : Random House Reference/House of Collectibles, 2008)
A guide to collecting state quarters that provides information on identifying mint errors, valuing a collection, and understanding the investment potential and provides profiles of each state and the stories behind the quarters' designs and creation.
Originally published as: The official guidebook to America's state quarters, c2000.
Includes bibliographical references (p. 244-249).
Adult
Keywords: Coins, American -- Collectors and collecting -- Handbooks, manuals, etc; Commemorative coins -- Collectors and collecting -- United States -- Handbooks, manuals, etc; Emblems, State -- United States -- Miscellanea; Quarter-dollar -- Collectors and collecting -- Handbooks, manuals, etc; Coins -- Collectors and collecting -- Handbooks, manuals, etc; Commemorative coins -- Collectors and collecting -- Handbooks, manuals, etc; Quarter-dollar -- Collectors and collecting -- Handbooks, manuals, etc; State emblems -- United States -- Miscellanea